Community forestry in Yunnan: the challenge for networks [Chinese] - Colchester, M. (Center for International Forestry Research, 2004)
China’s south-western province of Yunnan is a mountainous area of high biological and cultural diversity that was annexed into China relatively late in Chinese history. The province has lost over two thirds of its original forest cover and lost half of what remained in the last fifty years. Ethnic minorities make up about a third of the population of the province but predominate in forested areas. Chinese policy towards ‘minority nationalities’ at first recognized their right to self-determination but since liberation has oscillated between assimilationist and integrationist approaches. Despite strong central government control, the law grants them an important measure of cultural and institutional autonomy at the local level. Nationally, forest policy has been highly centralized and geared towards timber production. Quota driven overharvesting has depleted forests and led to serious soil erosion, local impoverishment, flooding and massive loss of life in the lowlands. While mass afforestation efforts have disappointed. Since 1998, the government has banned logging in Yunnan, allowing only a very restricted cut for domestic use. Imprudent natural resource use is linked to the doctrine of State ownership of all lands and forests and the imposed structure of village collectives. Since the late 1970s, the government has progressively devolved land and then forests to local farmers to manage and enjoy use rights to. Massive increases in agricultural production have resulted, but the lesser degree of autonomy granted farmers with respect to forest land, combined with the top-down quota system, inadequate supervision capacity, poor delineation of forests and the slower rate of return on investment have frustrated social forestry initiatives. Farmers’ skepticism that devolved tenure would really give them rights over timber has been confirmed by the logging ban. At the same time, in Yunnan, many upland farmers are being obliged to plant trees on their higher fields, with the aim of limiting run-off. The simultaneous loss of grain for subsistence and income from timber has hit farmers hard. The losses have not been made up with subsidies and grain handouts. Local activists distinguish between the government’s ‘social forestry’ and the ‘community forestry’ that has been promoted, since the late 1980s, by the Ford Foundation, international development assistance projects and the international networks, notably RECOFTC. Despite major advances in awareness raising, training, the development of forestry school courses and curricula, and despite numerous educational pilot projects, community forestry has not yet ‘taken off’ in the province. This can only come when the central government’s policy changes. Laws restricting civil society organizations are quite strict in China, yet despite these limitations an incipient provincial level network has evolved promoting participatory approaches to development. Efforts to promote a national level community forestry network have been less successful. Although Yunnan has had a relatively limited experience with international community forestry networks, local actors provide highly insightful lessons and suggestions about how such networking should be improved. International networking is valued as a source of information and inspiration but should be made more interactive, locally driven and strategic. The main challenges now facing community forestry in Yunnan are achieving national policy reform, and building local capacity and awareness in both communities and forestry bureaux. Recent government moves to allow village level democracy and slim down the administration offer opportunities to give farmers greater initiative. Perhaps minority areas, where indigenous forest related knowledge is retained, and where more autonomy is, notionally, allowed, offer hopeful beginnings.